Compressive behavior of FRP-confined reinforced concrete columns. (1st February 2017) - Eid, Rami; Paultre, Patrick
Highlights: A unified stress-strain model for FRP-confined concrete is proposed. The model takes into account the interaction between the transverse steel and FRP. The model is suitable for circular and rectangular reinforced-concrete columns. Experimental study was conducted to examine the steel-/FRP confinement action. Model and experimental results are in good agreement. Abstract: The evolution of earthquake-resistance standards has led to introduction of new design equations for the amount of transverse steel reinforcement (TSR) to ensure ductile behavior of reinforced-concrete columns. In order to comply with the new codes' TSR requirements there is a need to strengthen existing columns. One of the methods to strengthen reinforced-concrete columns is by using fibre-reinforced polymer (FRP) composites as confinement reinforcement. Critical reviews of existing studies pertaining to the fundamental behavior and analytical modelling of FRP-confined concrete columns have indicated that there are several aspects on which more research is required. These include, amongst others, the interaction between the internal transverse reinforcement confinement and the external FRP confinement, and non-uniform confinement as found in FRP-confined square/rectangular sections. This paper presents the development of a unified stress-strain model suitable to represent the axial behavior of circular and square/rectangular reinforced-concrete columns confined internally with TSR, externally with FRP, or both internally and externally with TSR and FRP, respectively. Moreover, experimental study of six FRP-/TSR-confined square reinforced-concrete columns under compressive axial loading was conducted. It is shown that stress-strain curves predicted by the proposed model are in good agreement with the presented as well as published experimental results.